2008
DOI: 10.1002/chem.200701258
|View full text |Cite
|
Sign up to set email alerts
|

RhIII‐ and IrIII‐Catalyzed Asymmetric Transfer Hydrogenation of Ketones in Water

Abstract: Asymmetric transfer hydrogenation (ATH) of ketones by formate in neat water is shown to be viable with Rh-TsDPEN and Ir-TsDPEN catalysts, derived in situ from [Cp*MCl2]2 (M=Rh, Ir) and TsDPEN. A variety of ketones were reduced, including nonfunctionalized aryl ketones, heteroaryl ketones, ketoesters, and unsaturated ketones. In comparison with Ir-TsDPEN and the related Ru II catalyst, the Rh III catalyst is most efficient in water, affording enantioselectivities of up to 99 % ee at substrate/catalyst (S/C) rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(125 citation statements)
references
References 164 publications
(134 reference statements)
7
118
0
Order By: Relevance
“…in 24 h). [128] Moreover, and in contrast to the related [RuClA C H T U N G T R E N N U N G (p-cymene)A C H T U N G T R E N N U N G (TsDPEN)], the activity of the iridium catalyst was completely inhibited in the HCO 2 H/ NEt 3 azeotrope. The rate of reduction was strongly pH dependent, with the highest TOFs achieved within a 2-unit window around pH 7.5.…”
Section: Ikariya and Co-workers Prepared The [Ircla C H T U N G T R Ementioning
confidence: 93%
“…in 24 h). [128] Moreover, and in contrast to the related [RuClA C H T U N G T R E N N U N G (p-cymene)A C H T U N G T R E N N U N G (TsDPEN)], the activity of the iridium catalyst was completely inhibited in the HCO 2 H/ NEt 3 azeotrope. The rate of reduction was strongly pH dependent, with the highest TOFs achieved within a 2-unit window around pH 7.5.…”
Section: Ikariya and Co-workers Prepared The [Ircla C H T U N G T R Ementioning
confidence: 93%
“…The combined organic extracts were combined, dried over magnesium sulfate and the organic solvent was removed under reduced pressure to leave the crude product as a pale yellow solid. The crude product was -2-(((1S,2S)-2-(4-methylphenylsulfonamido)-1,2diphenylethyl)-carbamoyl)pyrrolidine-1-carboxylate (19): N-tBoc-(L)-proline (500 mg, 2.33 mmol) and triethylamine (1.1 cm 3 ) were dissolved in anhydrous THF (11.7 cm 3 ) and cooled to 0 °C. Ethyl chloroformate (0.24 cm 3 , 2.5 mmol) was added and the mixture was stirred at 0 °C for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…[16e,i,j] The ATH of ketones in water [17] has been the subject of a number of studies. [18,19] In 2004 Xiao [20] found that the use of a ruthenium (pcymene) TsDPEN catalyst ((S,S)-1) in water exhibited good catalytic activity when using sodium formate as the hydrogen donor. [21,22] The pH of the reaction had a pivotal effect; at low pH, the nitrogen atom adjacent to the tosyl group protonates and becomes detached from the metal centre, thus reducing activity, whilst at higher pH the ligand-metal bonding remains intact.…”
Section: Introductionmentioning
confidence: 99%
“…very often applying Ru(II)-based homogeneous catalysts. Excellent rates and selectivities were achieved by Noyori [37], Bäckvall [8], Xiao [38] and others in synthesis of secondary alcohols. In general, water is not well tolerated in such processes [38], and several studies showed that both the rates and selectivities decrease substantially with increasing water content of the 2-propanol-water mixtures even in those cases when watersoluble catalysts were applied.…”
Section: Introductionmentioning
confidence: 93%
“…Excellent rates and selectivities were achieved by Noyori [37], Bäckvall [8], Xiao [38] and others in synthesis of secondary alcohols. In general, water is not well tolerated in such processes [38], and several studies showed that both the rates and selectivities decrease substantially with increasing water content of the 2-propanol-water mixtures even in those cases when watersoluble catalysts were applied. Notable exceptions are the transfer hydrogenations of ketones studied by Williams et al [39,40] and by Ajjou and Pinet [11] where up to 51% (v/v) water could be applied beneficially.…”
Section: Introductionmentioning
confidence: 93%